The Level of SDGs Disclosure Practice by Government Link Companies in Malaysia: A Conceptual Exploration - Zaini, Syeliya Md; Fahm, Fadzlina Mohd; Noruddin, Nur Adura Ahmad; Besar, Mohd Hairul Azrin Hj; Razak, Ahmad Lutfi Abdul (Journal of Accounting, Business and Management (JABM), 2024)
This concept paper explores the level of Sustainability Development Goals (SDGs) Disclosure practices by Government Link Companies in Malaysia in the current business environment. This study is designed to examine the level of SDG disclosure practices in companies’ corporate reporting by examining the level of Malaysian Government Link Companies (GLCs) SDG disclosure practices with publicly listed companies based on their industry segments. Drawing from the stakeholder theory, this study highlights the influence of ownership structure and board diversity, which can play an essential role in shaping the companies’ practices for SDG disclosure. Through a comprehensive review of the existing literature, the paper unravels the distinctive SDG commitments due to internal and external drivers, particularly in the country with higher concentrated ownership structures. Using stakeholder theory, a set of hypothesised relationships between SDG disclosure practices and drivers for disclosure are developed. The study emphasised the importance of nuanced understanding to improve corporate sustainability practices, accountability, and value creation. The study aims to guide future research for robust Sustainable Development Goal disclosure practices measurements framework and identify the challenges of such practices in a given economic situation. This paper's conceptual framework and discussions are intended to contribute to a broader academic discourse on the rising concern of SDG practices for economic decision-making.